(untitled) (Journal of Social Sciences Review, 2023)
Methamphetamine is a toxic and powerful drug which is popularly known as ’ice’ in Pakistan. The use of ice has increased in the last decade in the Khyber Pakhtunkhwa (KP) province of Pakistan. Objective: The objective of the current qualitative study was to explore the impact of methamphetamine on the social and economic condition of addicts in KP, Pakistan. Method: A total of 14 Anti Narcotic Force and Drug Rehabilitation Centers officials were selected through a purposive sampling technique, in Peshawar, Pakistan. For the collection of data, a self-designed interview guide was used. Results: The study found that the addicts faced multiple social and economic problems which includes social stigma, breakage of social relationships or isolation, selling of own valuables, stealing of valuables and becoming a drug peddler to finance his/her drug habit. Conclusions: The study recommends that the government may aware the public about the toxicity and misconceptions of methamphetamine use and family also may play a significant role in the prevention of methamphetamine use.